FAKTOR - FAKTOR YANG BERPENGARUH TERHADAP KEPUASAN PASIEN PADA PELAYANAN PENGOBATAN TB PARU DI BKPM KOTA PEKALONGAN - Sri Hidayati; Ahmad Baequny; Sumarni Sumarni (Badan Perencanaan Pembangunan, Penelitian dan Pengembangan Daerah (Bappeda) Kota Pekalongan, 2016)
NEW CASES OF PULMONARY TB ARE STILL HIGH ENOUGH AT PEKALONGAN CITY, INCIDENT OF DROP OUT/DEFAULT ALSO STILL HIGH (17,3%) BECAUSE NATIONAL TARGETS SHOULD BE UNDER 5%. THE NUMBER OF RECOVERY STILL UNDER NATIONAL TARGETS TOO BECAUSE IT LACKS OF 85%.PAST MEDICAL TREATMENT OF PULMONARY TUBERCULOSIS CAN CAUSE KLIEN DROP OUT. TO SOLVE THAT PROBLEM, IT IS NEEDED PLACE OF HEALTH SERVICES THAT GIVES SERVICES APPROPRIATE WITH NECESSITY AND PATIENT HOPE, SO PATIENT FEEL SATISFY AND DISPOSED WILL FOLLOW MEDICAL PROGRAM THAT TO BE PERFORMED. THE AIM OF THIS RESEARCH WAS TO ANALYZE FACTORS THAT INFLUENTIAL TOWARD PATIENT SATISFACTION ON MEDICAL SERVICES OF PULMONARY TB AT BKPM PEKALONGAN CITY. THIS RESEARCH WAS DESCRIPTIVE ANALYTIC WITH CROSS SECTIONAL DESIGN. POPULATION OF THIS STUDY WAS ALL OF PATIENTS WHO SUFFERED FROM TBC (POSITIVE BTA). THEY WERE PERFORMING MEDICAL PROGRAM OF TBC AT BKPM PEKALONGAN CITY WITH TOTAL NUMBER OF 80 PERSONS. COLLECTING DATA WAS DONE WITH QUESTIONNAIRE. DATA WERE ANALYZED WITH CHI SQUARE TEST AND LOGISTIC REGRESSION. THE RESULT OF THIS RESEARCH SHOWED THAT THERE WERE RELATIONSHIP BETWEEN EDUCATION, EMPLOYMENT, KNOWLEDGE AND PATIENT’S ATTITUDE ON MEDICAL SERVICES OF PULMONARY TB AT BKPM PEKALONGAN CITY. RESULT OF MULTIVARIATE SHOWED THE MOST FACTOR INFLUENTIAL WAS ATTITUDE (OR = 19,801) AND EDUCATION (OR = 6,637). IT IS RECOMMENDED FOR BKPM PEKALONGAN CITY TO INCREASE SERVICES ON GIVING EXPLANATION, VELOCITY, SANITATION, AND COMFORT FOR MEDICAL SERVICES OF PULMONARY TB IN ORDER TO INCREASE PATIENT SATISFACTION.